Uncommon Occurrence of an Air Embolism during the Preanhepatic Phase of an Orthotopic Liver Transplant - Klint J. Smart; Saman Yaghoubian (Case Reports in Anesthesiology)
Vascular air embolism (VAE) during liver transplantation usually occurs during the dissection phase of the procedure or during liver reperfusion. If this phenomenon occurs, it can cause significant cardiovascular, pulmonary, and neurological complications. Prompt identification of VAE is essential, and the surgeon should be immediately notified. The mainstay treatment is identification and rectification of the source of the air embolus, hemodynamic support, and prevention of further air entrainment. This case report describes the occurrence of a pulmonary air embolism during the preanhepatic phase of an orthotopic liver transplant.